pengaruh stres pengaruh stres kerja terhadap kinerja karyawan di universitas muhammadiyah palopo : pengaruh stres kerja terhadap kinerja karyawan universitas muhammadiyah palopo - nurlela; haedar; lita sriyanti (Universitas Slamet Riyadi, 2024)
This research aims to determine the effect of work stress on employee performance at Muhammadiyah University of Palopo. This research was conducted using quantitative methods. The population and sample used were all employees, totaling 34 employees. The sample in the study used a saturated sampling technique, namely all employees of the Muhammadiyah University of Palopo. The data used in this research is primary data in the form of a questionnaire. From this research it was found that there is an influence between the work stress variable (X) on employee performance (Y). This is proven through hypothesis testing using the t test. Where the results obtained with t count are greater than t table, namely t count (3.493) > t table (1.694). So H1 is accepted or